Analysis of the Social and Environmental Impacts of Broiler Chicken Farms in Tuncung Village, Maiwa District, Enrekang Regency - Muhammad Agussalim; Armayani; Angga Nugraha (Global Writing Academica Researching and Publishing, 2026)
The presence of broiler chicken farms in Tuncung Village, Maiwa District, Enrekang Regency, has social and environmental impacts on the local community. This study aims to analyze these social and environmental impacts and to determine the community's response and attitude toward the farms' presence. A descriptive quantitative approach was employed, involving 93 respondents selected through purposive sampling. Data were collected via questionnaires using a three-point Likert scale (agree, undecided, and disagree) and subsequently analyzed descriptively using IBM SPSS Statistics. The results indicate that the social impact falls into the moderate category, with an average score of 72%, reflected in changes to social interactions, public perception, and the potential for social conflict. The environmental impact also falls into the moderate category, with an average score of 75%, encompassing issues such as odor, farm waste, and reduced environmental comfort. Meanwhile, the community's response and attitude fall into the